TRANSLATION AND ITS CROSS-CULTURAL RELEVANCE - Ergasheva, Nigora Erkin qizi (Educational Research in Universal Sciences, 2023)
The process of translation has had a significant impact on the relations of nations and countries, as it is the major factor of communication. Translation is also considered as a bridge of communication among nations that have unique culture and language. Inadequate knowledge of another culture may probably cause confusion, frustration or backlash during communication process, which can lead unsuccessful attempt of agreement. Therefore, it should be focused on creating intercultural communication in order to conduct effective conversation. This article analyzes the historical, social and cultural features of translation by combining the standards of cross-cultural communication. This article explores problems of rendering texts and speeches considering the cultural gap between distinct countries, seeks solutions and evaluates the role of interpreter in the process of translation.